MENTAL HEALTH PHENOMENA OF STUDENTS FROM BROKEN HOME FAMILIES IN MAN 2 MEDAN MODEL - Nabila Nabila; Zainun Zainun (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
The family is the first and main place of learning for children. However, not all families can be a comfortable learning place forchildren, especially broken home families. Broken home students are vulnerable to mental health problems and need to get the rightsupport. This research aims to determine the mental health condition of students who experience broken homes due to their parents' divorce. The method used in this research is a qualitative method with a descriptive qualitative approach. The data collectiontechniques used were observation, interviews and documentation. The research results showed that five MAN 2 Model Medanstudents accepted their parents' divorce, but it had an impact on the students' mental health conditions. This is indicated by changes in students' emotional, social and behavioral changes. Apart from that, there are also developments experienced bystudents which are supported by several external and internal factors.